(untitled) (Shahroud Journal of Medical Sciences, 2016)
Background: Induced pluripotent stem cells (iPSCS) can be obtained from autologous cells for therapeutic purposes. So, far, many studies have been done to produce induced pluripotent cells by transferring specific pluripotency genes using different methods. In this study, pluripotency gene expression induced by external stresses was assessed in cord blood mononuclear cells.Methods: In this experimental study, mononuclear cells were isolated from umbilical cord blood. Isolated cells were divided into three groups. The first group had been exposed to HCL (pH 5.7) for 25 minutes and then transferred to the medium with normal pH. The second group was triturated with hamilton syringe for 15 min (external pressure), and the last group was considered the control group and did not receive treatment. Then, total RNA was extracted on Day 7. Gene expression of OCT4, SOX2, NANOG, REX1, and KLF4 was evaluated using qRT-PCR.Results: Gene expression of OCT4, NANOG, REX1, and KLF4 was increased after exposure to acidic pH and external pressures in comparison with control cells (P < 0.05). SOX2 gene expression was decreased in cells exposed to acidic pH but increased by external pressure.Conclusions: Exposure of umbilical cord blood mononuclear cells to acidic pH and external pressure lead to re-activation of pluripotency genes in mature cells. These findings indicate that mature cells may be reprogrammed with manipulation of environmental conditions.